Oral health status of adult heart transplant recipients in China: A cross-sectional study. Issue 38 (September 2018) - Cao, Ying; Chen, Xi; Jia, Yixin; Lv, Yalin; Sun, Zheng
Abstract : Abstract: Limited information on the oral health status of adult heart transplant recipients (HTRs) is known, and no available data exist in China. A prerequisite dental evaluation is usually recommended for patients' postorgan transplantation because lifelong immunosuppression may predispose them to infection spread. The aim of this study was to investigate the oral health status of Chinese adult HTRs and determine the association between oral health status and history of heart transplantation (HT). We carried out a cross-sectional study to collect clinical, demographic, socioeconomic, and behavioral data from 81 adult patients who received heart transplantation during 2014 to 2015 in China. Clinical examinations for the presence of dental plaque, dental calculus, dental caries, and periodontal health conditions were performed in a standardized manner by one trained examiner. Sociodemographic, socioeconomic, and behavioral data were self-reported using questionnaires. The prevalence of the above conditions was compared with 63 age- and sex-matched controls. General liner regression analysis was used to assess associations between mean number of decayed, missing, and filled teeth (DMFT) and mean community periodontal index of treatment needs (CPITN) scores and history of heart transplant. Mean age of the HT group was 47.7 ± 12.2 years and men accounted for 69.1% of the sample. The overall median DMFT score in the HT group was 3 (1–5) and caries prevalence was 80.2%, which were similar to the control group ( P  > .05). The overall mean CPITN score of the HT group was 1.84, which was significantly higher than the control group (1.07, P  = .001). Participants in the HT group had worse oral hygiene status and more teeth with probing depth ≥ 4 mm than controls (P = .043). Compared with participants who had no history of heart transplantation, HTRs presented worse periodontal health conditions (mean CPITN score, adjusted odds ratio (OR) = 1.39, 95% confidence interval (CI) = 1.12–1.71, P  = .003) and similar dental caries status (DMFT score, adjusted OR = 0.58, 95% CI = 0.37–0.91, P  = .058). Periodontal health status was positively associated with history of heart transplantation in Chinese adult HTRs.